AI Guardrails: Best Practices for Ethical, Safe, and Effective Deployment - Bhatia, Panav (Journal of Research in Science and Engineering, 2026)
As artificial intelligence (AI) continues to permeate various sectors, organizations must prioritize ethical, secure, and societally beneficial AI systems. This white paper provides comprehensive guidelines and guardrails across key domains—ranging from transparency and bias mitigation to security hardening and user-centric design. By adopting these recommended practices, organizations can ensure that their AI initiatives are both innovative and aligned with broader societal values.